خزعة المبيض لتأكيد تشخيص المبيض متعدد الكيسات - Hassan, Mais (Latakia University Journal -Medical Sciences Series, 2019)
خزعة المبيض لتأكيد تشخيص المبيض متعدد الكيسات This study was included 48 patients who have Polycystic ovary syndrome depending on the standard of Rotterdam , in the presence of infertility ( initial or secondary ) with another of the criteria for this syndrome diagnosed according to Rotterdam. We prepare patients for laparoscopy in the fifth day of the next menstrual cycle , ovarian biopsy was taken and sent for histological study. • The histological manifestations that have been reached: The existence of expanding cystic follicles 76.60%, primary follicles gathered by 82.98% Absence of a luteum or albicantia corpus 80.85%, A dense fibrous capsule by 85.11% The absence of development follicles by 87.23% , The thickness of the theca 70.21% , Presence the luteum cells within the follicular theca by 12.77% . • The results of the histological study of ovarian biopsy was : Fibrosis Ovary of 4.25% , Polycystic Ovary 76.59%, doubt Polycystic ovary by 4.25% , Endomitriosis by 4.25% , ovary failure 2.12% , ovary cyst 8.51%. • Accompanied by ovarian biopsy and Ultrasound Appearance in the diagnosis of polycystic ovary syndrome 77.78% . • Ovarian biopsy coincided with positive hormonal examination in the diagnosis of PCOS 72.22% . • comparison between the three methods used in the diagnosis of polycystic ovary syndrome using the average test and determine the value of the impact, we find that the best method and most accurate in the diagnosis of PCOS is ovarian biopsy with high impact value (0.910) then ultrasound and finally hormonal analysis. أجريت هذه الدراسة على (48) مريضة ممن شخص لديهن متلازمة المبيض متعدد الكيسات اعتماداً على معيار روتردام ، وذلك بوجود العقم ( البدئي أو الثانوي ) كشكوى أساسية مـع معيار آخـر مـن المعايير المشخصة لهذه المتلازمة وفق روتردام. قمنـا بتحضير المريضات تخديرياً و جراحياً لإجراء تنظير بطن و ذلك فـــي اليوم الخـامس مـن الدورة الطمثية التالية، وتـم أخذ خزعــــة مبيضية وإرسالها للدراسة النسيجية . كانت المظاهر النسيجية التي تم التوصل إليها : وجــود جريبات كيسية متوسعـــة بنسبــة 76.60% ، تجمع الجريبــات البدئية بنسبة 82.98% غيــــاب الجسم الأصفر أو الأبيض بنسبـــة 80.85%، محفظــة ليفيــة كثيفـــة بنسبة 85.11% غيــاب الجريبات المتطورة بنسبة 87.23% ، سماكــة اللحمة المبيضية بنسبة 70.21% وجود خلايا لوتينية ضمن القراب الجريبي بنسبة 12.77% . توزعت نتائج الدراسة النسيجية للخزعة المبيضية كما يلي : تليف مبيض بنسبة 4.25% , مبيض متعدد الكيسات بنسبة 76.59% ، شك مبيض متعدد الكيسات بنسبة 4.25% ، إندومتريوز بنسبة 4.25% ، قصور مبيض بنسبة 2.12% ،كيسة مبيض بنسبة 8.51% . ترافقت الخزعة المبيضية والموجودات الصدوية في تشخيص متلازمة المبيض متعدد الكيسات بنسبة 77.78% . ترافقت الخزعة المبيضية مـــع إيجابية الفحص الهرموني فـــي تشخيص PCOS بنسبة 72.22% . بالمقارنة بين الوسائل الثلاث المتبعة في تشخيص متلازمة المبيض متعدد الكيسات باستخدام اختبار المتوسط و تحديد قيمة الأثر ، نجد أن أفضل الوسائل و أدقها في تشخيص PCOS هي الخزعة المبيضية بقيمة أثر مرتفعة ( 0.910 ) ثم التصوير بالأمواج فوق الصوتية وأخيراً التحاليل الهرمونية .